If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -2) = 5x + 12 Reorder the terms: 3(-2 + x) = 5x + 12 (-2 * 3 + x * 3) = 5x + 12 (-6 + 3x) = 5x + 12 Reorder the terms: -6 + 3x = 12 + 5x Solving -6 + 3x = 12 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -6 + 3x + -5x = 12 + 5x + -5x Combine like terms: 3x + -5x = -2x -6 + -2x = 12 + 5x + -5x Combine like terms: 5x + -5x = 0 -6 + -2x = 12 + 0 -6 + -2x = 12 Add '6' to each side of the equation. -6 + 6 + -2x = 12 + 6 Combine like terms: -6 + 6 = 0 0 + -2x = 12 + 6 -2x = 12 + 6 Combine like terms: 12 + 6 = 18 -2x = 18 Divide each side by '-2'. x = -9 Simplifying x = -9
| 2cx+4dx= | | 3/1-1/3 | | 3-1/3 | | x^3-4=3 | | 4x^2-21x+42=6x+7 | | x^2+12x+21=3x+3 | | X*(4/100)+X=205 | | 2y^2+y=-11y | | x^2-11x-1=0 | | 5x+26=14x-83 | | X+(4*X)/100=0 | | y-6=-y^2 | | 3x^2-21x-6=0 | | y=-8-3x/2 | | X+(4*X)/100 | | X+(X*4/100)=205 | | [x+4]+8=2 | | abs(x-4)=5 | | Ix-4l=5 | | x^2+2.4x+0.4=0 | | y^2-7y-44=0 | | 6x-17=10x-53 | | 5*1/2y-3=9 | | 3*-17=10*-53 | | 4p+3q=28 | | 6x+21=14x-15 | | 3x-17=10x-53 | | 7(3/4y)-3y=-2 | | 14/13=n/11 | | 2x^4-10x^2-12=0 | | 3145x-103y=1 | | 4/5=n/18 |